Safety and efficacy of tandem hemodialysis and plasma exchange in children - Schäfer, Betti; Ujszaszi, Akos; Schäfer, Susanne; Heckert, Karl Heinz; Schaefer, Franz; Schmitt, Claus P. (Clinical journal of the American Society of Nephrology, 2014)
Background and objectives Patients with immune-mediated kidney disease and liver failure often require plasma exchange (PE) and hemodialysis (HD). Combining both methods (i.e., connecting the PE and HD circuits in series [tandem dialysis]) should allow for a more efficient treatment. This work reviews the authors’ experience with tandem blood purification. - Design, setting, participants, & measurements Chart review was utilized to retrospectively analyze the efficacy and tolerability of 92 combined PE/HD (cPE/HD) sessions in 26 children in comparison with 113 sequential PE/HD (sPE/HD) treatments performed in 32 children between 1988 and 2012 at the University of Heidelberg Center for Pediatric and Adolescent Medicine. Eleven children received both treatment modalities. - Results The mean treatment duration was 3.8±2.2 hours per cPE/HD and 5.9±1.6 hours per sPE/HD session (P<0.001). Dialyzer surface areas per body surface area (in meters squared) and blood flow rates were similar. Although a 3-fold higher initial bolus of heparin was administered with cPE/HD, the heparin dose per hour was similar with both modalities and the total heparin load was only slightly lower with cPE/HD, with a median 2939 IU/m2 per session (interquartile range, 1868, 4189) versus 3341 IU/m2 per session (interquartile range, 2126, 4792). In sessions with regional anticoagulation, equal citrate and calcium infusion rates were applied. Plasma turnover, ultrafiltration rates, and solute removal were comparable. Procedure-related problems developed in 14.0% of cPE/HD and 7.0% of sPE/HD sessions (P=0.37). Clinical symptoms occurred in 19.6% and 6.2% (P=0.05), necessitating treatment discontinuation in 12.0% and 5.3% of the sessions (P=0.14). Intra-individual comparison of both dialysis methods in 11 children reconfirmed these findings. - Conclusions cPE/HD is a time-saving procedure relative to sPE/HD, but may be associated with a higher rate of procedure-related and clinical adverse events.